Exploring the potential of coffee cherry peel flour (Coffea arabica) and banana peel liquid (Musa Ã— paradisiaca) as substitutes in rolled bolu cake - Sondak, Michael Ricky; Ngawi, Imelda Agustina (AGROMIX, 2024)
Introduction: This research intends to investigate the potential of coffee cherry peel flour and banana peel liquid as cake-baking alternatives, taking into account both their chemical qualities and organoleptic reactions. Methods: This experimental study uses baking and steaming techniques to analyze coffee cherry peel flour and banana peel liquid. Chemical analysis of carbohydrates, protein, fiber, moisture, ash, and fat content is conducted, along with organoleptic analysis of color, fragrance, taste, and texture. The ANOVA method is used for data analysis. Results: According to the research findings, the greatest results are obtained when baking a cake using a mixture of 50% coffee cherry peel flour and 30% banana peel liquid. The cake has a chemical composition characterized by the presence of 28.9% carbohydrate, 4.02% protein, 6.23% fiber, 25.2% moisture content, 0.45% ash content, and 41.5% fat content. The organoleptic testing results indicate that this cake has received a favorable rating in terms of color (5.49 on the liking scale), scent (5.60 indicating very high liking), taste (5.44 indicating liking), and texture (5.31 indicating liking).Conclusion: The research results show that a 50% concentration of coffee cherry peel flour and a 30% banana peel liquid considerably change all organoleptic characteristics of the cake. The cake prepared using these specific proportions exhibits desirable attributes, including a well-received brown hue, a typical coffee fragrance, a discernible coffee flavor, and a tender and readily chewable consistency.